THE RECOVERY TECHNOLOGY THREADED MOUNTING OF AXLE-SITE CAR - Matviienko, O. O. (Science and Transport Progress, 2007)
The article describes a method of renewing screw-thread connection of parts of the journal-box car unit with the use of method of repair sizes, when the more valuable part (the axle) is renewed by mechanical treatment, while the adjoining part (butt end nut) is replaced with a new one of a repair size.